Implementation of Quality Management Curriculum in Arabic Learning - Ulin Nuha, Muhammad Afthon; Musyafa’ah, Nurul (Institut Agama Islam Negeri Curup, 2022)
This research aimed to understand the curriculum quality management more deeply, to understand the scope of learning Arabic, and to know the process of curriculum quality management and Arabic learning. The researcher used a descriptive approach by suggesting several definitions of curriculum quality management and its application in learning Arabic. The data collection method deployed the study of literature and documentation. In analyzing the data, the researcher analyzed books or articles related to curriculum quality management, opinions from experts in the world of Arabic education and curriculum, theories in Arabic learning, and suggestions and criticisms addressed in the research. The results of this study demonstrated that 1) curriculum quality management in learning, in general, is an effort as effective and efficient as possible to achieve a curriculum goal without a quality approach in the curriculum. 2) Learning, in general, can be said as education which is a process of guiding students so that they can develop sufficiently, and they can contribute amid life. 3) To see the progress of learning, students must be assessed through a process that is made by national standards and includes various cognitive, affective, and psychomotor aspects as well as other psychological aspects. The formal finding from this research exhibited that the benchmarking of Arabic learning in this discussion uses the